2014
DOI: 10.1253/circj.cj-14-0327
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Tissue Doppler Imaging-Derived Atrial Conduction Time Can Predict Postoperative Atrial Fibrillation in Patients Undergoing Aortic Valve Replacement for Aortic Valve Stenosis

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp and postoperative complications and requirements, have been evaluated as predictors of POAF; however, most of these predictors were not consistent among studies and only advanced age was a consistent predictor. 6 Recently, echocardiographic assessments have achieved much better prediction of POAF by measuring the left atrium-related values including the left atrial volume index (LAVI), LA strain and total atrial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 40 publications
(34 reference statements)
2
26
1
1
Order By: Relevance
“…6 In our previous study in patients undergoing off-pump CABG and aortic valve surgery, the optimal PA-TDI duration cut-offs for predicting POAF were 141 and 147.3 ms, respectively. 7, 8 In the present study, we found that the optimal cut-off for PA-TDI duration was >159.4 ms. The difference in optimal PA-TDI cut-off may be related to the size of the LA and degree of surgical manipulation, and thus the optimal cut-off should be evaluated separately.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…6 In our previous study in patients undergoing off-pump CABG and aortic valve surgery, the optimal PA-TDI duration cut-offs for predicting POAF were 141 and 147.3 ms, respectively. 7, 8 In the present study, we found that the optimal cut-off for PA-TDI duration was >159.4 ms. The difference in optimal PA-TDI cut-off may be related to the size of the LA and degree of surgical manipulation, and thus the optimal cut-off should be evaluated separately.…”
Section: Discussionsupporting
confidence: 49%
“…15 In the present study, there was no significant difference in LAVI between patients with and without POAF, but LAVI in both groups was larger than that in previous reports, and both groups in the present study had an increased risk of POAF. 3,7, 8 TACT is defined as the time between the initial and the last portion of the atrial myocardium to depolarize, which usually reflects the interval from the sinus node to LA wall activation, and this was discussed in our previous reports. 5,7,8 Theoretically, TACT is measured by the duration of the P wave on 12-lead surface ECG, but there are several reports that measured TACT on echocardiography.…”
Section: Preoperative Ecg and Echocardiographymentioning
confidence: 99%
See 3 more Smart Citations